Pendampingan Pembuatan Perencanaan Strategis Program Pemberdayaan Kesejahteraan Keluarga di Kota Bekasi - Tussoleha Rony, Zahara; Aryanto, Sani; Christine Simboro, Maria (Jurnal Pengabdian Masyarakat dan Penelitian Terapan, 2023)
Abstract: Every organization that wants to realize its organizational goals is obliged to make effective plans including social organizations, namely the Family Welfare Empowerment (PKK) which is a national community organization. PKK is a Government Partner and Community Organization, which functions as a facilitator, planner, implementer, controller and driver at each level for the implementation of the PKK program. The heavy and noble task of the PKK organization is to make the PKK chairman its members and need to understand their functions and roles as well as job descriptions.All of these leaders have tasks that are not easy, especially during the pandemic and post-pandemic conditions, many plans have not been realized or even been ineffective. The needs of society are largely changing. Therefore an evaluation and review of the 2021 and 2022 programs is needed. In order for planning to be focused and in accordance with the needs of the city of Bekasi, training and assistance are needed in making work plans in the PKK organization which begins with making SWOT. Standard Operating Procedure, as well. The results of the training and planning are expected to increase the competence of PKK administrators in making appropriate SWOT and planning in accordance with organizational goals and this is evidenced by the output of the training, namely several SOP and work planning programs. Abstrak: Setiap organisasi yang ingin mewujudkan tujuan organisasinya wajib membuat perencanaan efektif tidak terkecuali organisasi sosial, yaitu Pemberdayaan Kesejahteraan Keluarga (PKK) yang merupakan organisasi masyarakat nasional. PKK adalah Mitra Kerja Pemerintah dan Organisasi Kemasyarakatan, yang berfungsi sebagai fasilitator, perencana, pelaksana, pengendali dan penggerak pada masing – masing jenjang demi terlaksananya program PKK. Tugas berat dan mulia dari organisasi PKK membuat ketua PKK anggotanya dan perlu memahami fungsi dan peran serta job deskripsinya. Semua para pimpinan ini memiliki tugas yang tidak mudah terlebih lagi kondisi pandemi dan pasca pandemi banyak perencanaan tidak terealisasi bahkan tidak tepat guna. Kebutuhan masyarakat sebagian besar berubah. Oleh karenanya dibutuhkan evaluasi dan review program 2021 dan 2022. Agar perencanaan dapat fokus dan sesuai dengan kebutuhan kota Bekasi diperlukan pelatihan dan pendampingan pembuatan perencanaan kerja di organisasi PKK yang diawali SWOT, dan prosedur operasi standar, serta. Hasil dari pelatihan dan perencanaan diharapkan meningkatkan kompetensi para pengurus PKK dalam membuat SWOT dan perencanaan yang tepat sesuai dengan tujuan organisasi dan hal ini dibuktikan dari output pelatihan yaitu beberapa SOP dan program perencanaan kerja.